Renal shear wave elastography in familial Mediterranean fever patients without nephropathy - Kök, Mehmet; Balkarlı Ayan, Ayşe; Ülgen, Sinan (The European Research Journal, 2025)
Objectives: Due to its lethal effects, early diagnosis of high risk patient groups for renal involvement especially amyloidosis is critical for Familial Mediterranean Fever (FMF). Amyloidosis, defined by the accumulation of extracellular amyloid protein material in the kidney, can reduce the elasticity of the renal parenchyma. Shear wave elastography (SWE) is a new ultrasonographic imaging modality that evaluates tissue elasticity. This pilot study assessed the renal parenchyma of FMF patients using SWE. Methods: Fifty-three FMF patients and 51 age- and sex-matched healthy control participants were included in this study. Participants with amyloidosis, estimated glomerular filtration rate (eGFR) less than 60 mL/min and/or signs of nephropathy (proteinuria, hematuria, renal tubular acidosis) were excluded. Routine history, physical, laboratory examinations (blood urea nitrogen, creatinine, C-reactive protein, urine dipstick test, spot proteinuria) and renal ultrasound were performed. SWE imaging was performed to measure renal parenchymal stiffness. Results: There was no significant correlation between SWE values (elasticity and velocity) and age, eGFR, serum blood urea nitrogen, and creatinine in the comparison of SWE findings of FMF patients and control groups. SWE values were statistically higher in FMF patients than in the control group (P=0.002 and P< 0.001 for elasticity and velocity, respectively). Conclusions: Increased renal stiffness in FMF patients may indicate early renal involvement (especially amyloidosis), suggesting SWE as a potential non-invasive diagnostic tool for early detection.